Systemic Insights for Value Creation in Solar PV Energy Markets: From Project Management to System Impacts - Javier A. Calderon-Tellez; Milton M. Herrera; Javier Sabogal-Aguilar; Melisa Tuirán; Sebastian Zapata (Energies)
Project management often overlooks the consideration of long-term effects that may impact sustainability transition and innovation. This paper addresses this gap by presenting an analysis that extends the traditional project life cycle model through the incorporation of a new phase, labelled “system impact”, which integrates innovation and sustainability into project management using a system dynamics methodology. To explore this extension, a simulation model is developed to analyse a solar photovoltaic (PV) power project, providing valuable insights into the systemic and dynamic impacts required for successful project outcomes, including effective benefits management and value creation. The results provide a sustainability-focused assessment of project success. Process innovation efficiency reaches its peak at 140 completed tasks, shortening the project duration from 18 to 13.25 months. This study highlights CO2 emission avoidance over 25 years compared to fossil fuel generators. Economically, despite an initial cost three times higher, the solar PV alternative proves more cost-effective in the long run, amounting to only 19% of the total cost of the fossil fuel option.